Critical Evaluation of Strategies for the Production of Blood Coagulation Factors in Plant-Based Systems - Top, Oguz; Geisen, Ulrich; Decker, Eva L.; Reski, Ralf (Frontiers in Plant Science, 2019)
The use of plants as production platforms for pharmaceutical proteins has been on the rise for the past two decades. The first marketed plant-made pharmaceutical, taliglucerase alfa against Gaucher’s disease produced in carrot cells by Pfizer/Protalix Biotherapeutics, was approved by the US Food and Drug Administration (FDA) in 2012. The advantages of plant systems are low cost and highly scalable biomass production compared to the fermentation systems, safety compared with other expression systems, as plant-based systems do not produce endotoxins, and the ability to perform complex eukaryotic post-translational modifications, e.g., N-glycosylation that can be further engineered to achieve humanized N-glycan structures. Although bleeding disorders affect only a small portion of the world population, costs of clotting factor concentrates impose a high financial burden on patients and healthcare systems. The majority of patients, ∼75% in the case of hemophilia, have no access to an adequate treatment. The necessity of large-scale and less expensive production of human blood coagulation factors, particularly factors associated with rare bleeding disorders, may be an important area for plant-based systems, as coagulation factors do not fit into the industry-favored production models. In this review, we explore previous studies on recombinant production of coagulation Factor II, VIII, IX, and XIII in different plant species. Production of bioactive FII and FIX in plants was not achieved yet due to complex post-translational modifications, including vitamin K-dependent γ-carboxylation and propeptide removal. Although plant-made FVIII and FXIII showed specific activities, there are no follow-up studies like pre-clinical/clinical trials. Significant progress has been achieved in oral delivery of bioencapsulated FVIII and FIX to induce immune tolerance in murine models of hemophilia A and B, resp. Potential strategies to overcome bottlenecks in the production systems are also addressed in this review.